The contest of administrative and l e a l status of political parlies in Ukraine - Глибіна, Ганна Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
In the article temrinology is specified on prohed questions, the concept of status and legal status turns out concepts are difteremiated administrative status and position, the concept of administrative status of political parties is determined.